Nonlinear propagation of incoherent white light in a photopolymerisable medium: From single self-trapped beams to 2-D and 3-D lattices - Kasala, Kailash (My University, 2012)
Optical beams that travel through a material without undergoing divergence are known as self-trapped beams. Self-trapping occurs when a beam induces a suitable index gradient in the medium that is capable of guiding the original beam. An incoherent light consists of femtosecond scale speckles, due to random phase fluctuations and were not thought to self-trap until recently. In 1997, Mitchell et al., showed that white light can self-trap, provided the medium cannot respond fast enough to form index gradients to these speckles individually. However, detailed studies have been hampered by a lack of suitable materials and strategies for enabling such a response. In 2006, our group showed that a photopolymer is suitable for incoherent self-trapping, since the index change is governed by an inherently slow rate of polymerization (of the order of milliseconds). This has enabled further studies of various phenomena with white light self-trapping.
The studies here show (i) the first direct experimental evidence of interactions of two incoherent white light self-trapped beams, as well as fission, fusion and repulsion. Existence of dark self-trapping beams with incoherent white light was also shown, counter intuitively in a positive nonlinear medium. (iii) Lattices were formed with multiple ordered bright as well as dark self-trapping filaments using optochemical self-organization. (iv) Woodpile-like 3D lattices with bright and dark beams were also demonstrated and simulations showed theoretical band gaps. (v) Self-trapping of a co-axial beam of incoherent white light was also shown experimentally and through simulations.
Keywords: Nonlinear propagation of incoherent white light; organosiloxane; photopolymer; optical self-trapping; optochemical self-organization; black and grey incoherent soliton; Atomic, Molecular and Optical Physics; Electromagnetics and photonics; Materials Chemistry; Optics; Polymer and Organic Materials; Polymer Chemistry; Semiconductor and Optical Materials; Atomic, Molecular and Optical Physics